Biodegradable polymers and constructs: A novel approach in drug delivery. (November 2019) - Prajapati, Shiv Kumar; Jain, Ankit; Jain, Aakanchha; Jain, Sourabh
Graphical abstract: Abstract: New polymers are continuously developed for new therapeutic applications. New and modified polymer chemistries that offer distinctive degradation and drug delivery are being identified and evaluated simultaneously. Biodegradable polymers have profound applications in drug delivery. For attaining sustained and controlled drug delivery, these polymers are modified to develop drug carriers such as nanoparticles, microparticles, microspheres, and matrix devices etc. This review explains the use of biodegradable polymers and their drug delivery systems for local or targeted and controlled/sustained drug/gene delivery. It explicitly presents various types of biodegradable polymers, their properties, and characterization parameters along with their promising pharmaceutical as well as drug delivery applications.